Crystal phase-driven copolymerization of CO2 and cyclohexene oxide in Prussian blue analogue nanosheets. (March 2022) - Zhang, Weibin; Fan, Touwen; Yang, Zhen; Yu, Ruipeng; Zeng, Xinjuan; Xu, Yonghang; Zhang, Min; Hu, Huawen; Ou, Jian Zhen; Zheng, Lirong
Highlights: Phase engineering of Prussian blue analogue (PBA) was realized by replacing H2 O with t BuOH. The rhombohedral phase appears as clusters within the amorphous support matrix. Catalytic CO2 -based copolymerization by PBA is crystal phase-dependent. The reaction pathway of the unique rhombohedral phase is revealed. Abstract: While the relatively complex chemical composition of Prussian blue analogues (PBAs) allows a high degree of flexibility in tuning the catalytic performances toward CO2 -based copolymerization, little is known regarding the influence of the crystal phase. Herein, we investigate the impact of the crystal phase tuning of the representative Zn−Co-based PBA on CO2 −epoxide copolymerization. The utilization of oxygen-containing tert ‑butanol molecules ( t BuOH) replaces water molecules from the Zn active center within the PBA-based nanosheets, inducing the crystal transformation from conventionally cubic to rhombohedral. The rhombohedral phase can be formed as clusters dispersed within the amorphous matrix, exhibiting the most active and selective CO2 −epoxide copolymerization performance with a turnover number of 31, 250 g/g Zn compared to that of long-range ordered cubic and rhombohedral counterparts. Such an improvement is ascribed to the abundant exposed Zn-O active centers enabled by the replacement of t BuOH molecules and rhombohedral coordination. Density functional theory calculation indicates different average adsorption energies for cyclohexene oxide (CHO) and CO2 (-5.45 vs. -0.02 eV) on the (001) surface, implying the initialization of copolymerization from the adsorption of CHO onto the Zn-O active centers. This work provides a feasible approach to enable on-demand manipulation of catalytic performances of emerging PBAs. Graphical abstract: Image, graphical abstract